Cannabidiol exerts multitarget immunomodulatory effects on PBMCs from individuals with psoriasis vulgaris - Pagano, Cristina; Ciaglia, Elena; Coppola, Laura; Lopardo, Valentina; Raimondo, Annunziata; Giuseppe, Monfrecola; Lembo, Serena; Laezza, Chiara; Bifulco, Maurizio (Frontiers in Immunology, 2024)
Introduction The involvement of endocannabinoid system (ECS) in the inflammatory cascade, and the ability of phytocannabinoids, endocannabinoids and their synthetic analogues to modulate it has become an interesting research area for new therapeutic approaches in inflammatory skin diseases. Cannabidiol (CBD) appears to be the most promising among phytocannabinoids, due to the lack of psychotropic effects and low toxicity profile. Its anti-inflammatory action has been highlighted in different preclinical models, ranging from experimental colitis to arthritis and neuroinflammation. Our aim was to evaluate CBD immune-modulatory effects in peripheral blood mononuclear cells (PBMC) of psoriasis individuals with particular attention to both innate and adaptative immune arms. Methods We performed in vitro immune functional experiments to analyze CBD action on various immune cells active in psoriatic lesions. Results The results showed that CBD produced a shift from Th1 to Th2 response, while boosting cytotoxic activity of Natural Killer (NK) cells. Furthermore, it also exerted a potent action on monocyte differentiation as, after CBD treatment, monocytes from psoriatic individuals were unable to migrate in response to inflammatory stimuli and to fully differentiate into mature dendritic cells. Finally, a M2 skewing of monocyte-derived macrophages by CBD also contributed to the fine tuning of the magnitude of immune responses. Conclusions These data uncover new potential immunomodulatory properties of this cannabinoid suggesting a possible therapeutic action in the treatment of multiple inflammatory skin diseases.